Lack of Association between Interleukin-1β Gene Polymorphism (rs16944) and Chronic Periodontitis: From a Case-Control Studies to an Updated Meta-Analysis - Hong, Seoung-Jin; Kang, Sang Wook; Kim, Su Kang; Kim, Young Sik; Ban, Ju Yeon (Disease Markers, 2018)
Background. Interleukin-1β (IL-1β) plays an important role as a mediator of various inflammatory responses in chronic periodontitis. Several studies have investigated the potential relationship between IL-1β polymorphism (rs16944) and susceptibility to chronic periodontitis; inflammatory process is involved, but conclusions is still controversial. Objective. The aim of this study was to determine whether the IL-1β polymorphism (rs16944) is associated with susceptibility to chronic periodontitis. Material and Methods. For the case-control study, 51 patients with chronic periodontitis and 33 healthy control patients were recruited in the study. Genotyping was conducted by direct sequencing. SNPStats and SPSS 18.0 were used for the analysis of genetic data and to evaluate odds ratios, 95% confidence intervals, and P values; logistic regression models were used. And to perform meta-analysis, studies about IL-1β polymorphism (rs16944) and chronic periodontitis were searched in PubMed, Embase, Google Scholar, and Korean Studies Information Service System (KISS) electronic databases until July 2017. Results. In our case-control study, no significant relationship was revealed between IL-1β polymorphism (rs16944) and chronic periodontitis (P>0.05 in each model). When combined with the previous studies in the meta-analysis, the result was not associated with chronic periodontitis in any of the models (CC vs. CT + TT: OR = 0.97, 95% CI = 0.762–1.246; CC + CT vs. TT: OR = 0.90, 95% CI = 0.658–1.232; and C vs. T: OR = 0.93, 95% CI = 0.774–1.128). The subgroup analysis stratified by ethnicity showed a weak association between the IL-1β polymorphism (rs16944) and chronic periodontitis in the Caucasian population (recessive model, OR = 1.34, 95% CI = 1.017–1.758, P=0.037). Conclusion. Evidences from a case-control study and the meta-analysis suggest that IL-1β polymorphism (rs16944) is not associated with susceptibility to chronic periodontitis.